Early Detection of Atrophy of Foot Muscles in Chinese Patients of Type 2 Diabetes Mellitus by High-Frequency Ultrasonography - Xiaohui Wang; Liang Chen; Weiwei Liu; Benli Su; Yuhong Zhang (Journal of Diabetes Research)
The aim of this study was to evaluate the diagnostic value of high-frequency ultrasonography in detecting atrophy of foot muscles in Chinese patients of type 2 diabetes mellitus (T2DM). Chinese patients of T2DM with (n=56) or without (n=50) diabetic peripheral neuropathy (DPN) and the control subjects (n=50) were enrolled. The nondominant foot of all subjects was examined with high-frequency ultrasonography. The transverse diameter, thickness, and cross-sectional area of the extensor digitorum brevis muscle (EDB) and the thickness of the muscles of the first interstitium (MILs) were measured. The results showed that the ultrasonographic transverse diameter, thickness, and cross-sectional area of EDB and the thickness of MILs in patients of T2DM with DPN were significantly smaller than those in patients of T2DM without DPN (all P<0.01) and those in the control subjects (all P<0.01). The transverse diameter and cross-sectional area of the EDB and thickness of MILs in patients of T2DM without DPN were significantly smaller than those of the control subjects (all P<0.01). In conclusion, the atrophy of foot muscle in Chinese T2DM patients can be detected by high-frequency ultrasonography. Notably, ultrasonography may detect early atrophy of foot muscles in patients without DPN.